How to write effective business English : your guide to excellent professional communication - Talbot, Fiona (Kogan Page Limited, 2019)
"How to Write Effective Business English gives guidance to both native and non-native English speakers on how to express yourself clearly and concisely. With case studies and real-life examples that demonstrate how English is used internationally in business, and full of ideas to help you get your communications right first time, this book sets the scene for describing the benefits of good Business English, ideal for multinational companies where communication is a priority. For native English speakers, it may mean un-learning things you were taught at school and learning how to save time by getting to the point more quickly in emails; for elementary to immediate English speakers, it focuses on the areas that are easy to get wrong. How to Write Effective Business English uses real-life international business scenarios to develop your skills and provide you with some answers that even your boss might not know. You will learn a system to help you quickly and easily write emails, letters, CVs and more. Featuring sections on punctuation and grammar, checklists to help assess progress and now with a new chapter on how to write effectively for social media, How to Write Effective Business English has been praised by both native and non-native writers of English as an indispensable resource"